Viskoznost: izbrani modeli in načini merjenja - Beltram, Vitja (Matrika, 2021)
This article presents selected aspects of dynamic viscosity of solutions. Interpretation of viscosity in solutions is presented, introducing four models explaining viscosity dependence on volume fraction. To connect mass concentration and volume fraction, intrinsic viscosity is introduced. Then, seven viscometers are presented which rely on Stokes' drag force or Poiseuille's law. Working principle of each viscometer in explained as well as their measuaring interval, sample consuption and measurement limitations. At the end, the selected relevance of viscosity in industry is presented, such as in farmaceutical industry, and how the viscosity of solution can be reduced by adding additives.
Keywords: fluid mechanics; measurement methods; mehanika tekočin; meritve viskoznosti; viscosity; viskoznost